Contribution of Islamic Commercial Bank Financing to East Java Economic Growth in the Era of Branchless Banking - Afandi, Muhammad Anif (Program Studi Ekonomi FEB UMY, 2021)
This study aims to determine and analyze the contribution of Islamic Commercial Bank’s (BUS) financing to the economic growth of East Java Province in the era of branchless banking. Three types of financing channeled by the BUS namely working capital financing, investment and consumption are used as the independent variables tested each effect on the dependent variable which is economic growth in East Java with a proxy of GDRP in the period of the quarter-I 2010 to quarter-I 2020. Ordinary Least Square (OLS) with dummy variable of branchless banking (0 = before the implementation of the branchless banking program (before November 2014) and 1 = after the implementation of the branchless banking program (after November 2014) is used as data analysis technique with the results of the study show that only consumer financing that have a positive and significant impact on economic growth of East Java. Whereas, the productive financing known to have positive impact but not significant toward the economic growth of East Java. Meanwhile, the branchless banking program known to give the positive and significant difference impact on economic growth in East Java compared to economic growth prior to the enactment of it. The results of this study beneficial for both the BUS and the regulator as an evaluation of the level of inclusiveness of the BUS’s financing to economic growth and the implementation of branchless banking in Islamic bank.